Academic vocabulary used by high school students in essays and its relation to English proficiency - Waluyo, Budi; Bakoko, Rahmah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Among the high number of studies on vocabulary, little attention has been given to high school students, even though EFL students begin to learn and use vocabulary in academic settings more complex at a high school level in non-English speaking countries. To fill this gap, this study examined high school students’ vocabulary use in English essay writing. The target words involved 70 among the most frequently occurring words in academic settings from the Academic Vocabulary List (AVL). The data set consisted of 233 essays collected in Thailand as part of an English proficiency test and analyzed using quantitative statistical analyses. The results of descriptive statistics disclosed the 48 words known and used by the high school students. The independent t-test and one-way ANOVA revealed the effects of gender and proficiency levels for certain words. Yet, students’ academic vocabulary knowledge and use were found to be unrelated to their writing achievement, overall English proficiency, and specific English skills including reading, speaking, and writing. It was assumed that nonacademic words might have played a more significant role in student essays than academic words did.